Analysis of methylation of a human X located gene which escapes X inactivation. - Mondello, C (1988)
The gene MIC2 is located in the pseudoautosomal region at the ends of the short arms of the X and Y chromosomes. In females MIC2 escapes X inactivation. We have analyzed the methylation pattern of MIC2 on the active X, the inactive X chromosomes, and the Y chromosome. The 5' end of the gene contains a GC rich region which is unmethylated on the active X, the inactive X and on the Y. The body of the gene is characterized by variable methylation.